APPROXIMATE STRING MATCHING UNTUK PENCARIAN KATA DALAM KAMUS BAHASA INDONESIA MENGGUNAKAN ALGORITMA JARO WINKLER - Vivi Sahfitri; Ibnu Batutah Zarizal (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2022)
Abstract : Language is the main thing in order to communicate with others both verbally and in writing. In language there is a meaning of words or sentences that can be accepted and understood if delivered with good and correct grammar. Dictionary is a tool used to know the meaning of a word. Currently, dictionaries are no longer conventional but are digital-based so that they can be accessed freely. This research aims to build a word search application in the dictionary Indonesian by applying the approximate String Matching method in word search on a Web-based Indonesian dictionary using jaro Winkler's algorithm. The research will also provide information about the time required by the system in string search, word suggestions, word meanings, sample sentences and images. Computational time testing results showed that jaro winkler's algorithm had a very effective quadratic runtime complexity on short strings. In addition, a lot of data in the database affects the search time but provides a word that is closer to the word searched. Functional testing to determine the performance of the software system shows that all parts of the system can run well according to the desired purpose when building the system.